The effect of water boundary conditions of advance face and lining on the evolution of internal forces in lining - J. Song; L. Miao; S. Feng (Lowland Technology International, 2015)
After tunnel excavation and lining installed, the excess pore pressures around tunnel dissipate over time, thus changing the soil effective stresses and leading to additional, time-dependent deformations. The deformation of soil around the tunnel can change the internal forces in lining. This study focuses on the effect of boundary conditions of advance face and lining on the internal forces in lining after tunnel excavation. The numerical model with specific geological conditions is established and the tunneling process is modeled by a step-by-step excavation using ABAQUS software. Four different cases were considered in the numerical model including permeable or impermeable boundary conditions of the lining and the advance face. From the calculation result the change mechanism of the internal forces in the lining after tunnel excavation are obtained. When the lining is impermeable the internal forces in the lining changes a little after tunnel excavation and when the lining is permeable the internal forces increased is dramatic. When the advance face is impermeable the increased internal forces in the lining are larger and when the tunnel is buried in large permeably soil the internal forces in the lining will be constant after tunnel excavation.